Parametric modeling, higher order FEA and experimental investigation of hat-stiffened composite panels. (15th September 2015) - Jin, Bo Cheng; Li, Xiaochen; Mier, Rodrigo; Pun, Adarsh; Joshi, Shiv; Nutt, Steven
Abstract: Sizing of hat-stiffened composite panels presents challenges because of the broad design hyperspace of geometric and material parameters available to designers. Fortunately, design tasks can be simplified by performing parameter sensitivity analysis a priori and by making design data available in terms of a few select parameters. In the present study, we describe parametric modeling and design sensitivity analyses performed on hat stiffener elements for both single and multiple-hat-stiffened panels using parametrically defined scripting finite element analysis (FEA) models and an idealized analytical solution. We fabricated a composite skin panel and 4 hat stiffeners using out of autoclave (OoA) and vacuum bag only (VBO) techniques. The stiffeners were subsequently bonded to the skin to form a multi-hat-stiffened panel. To validate the FEA and analytical solutions, multi-point deflections were measured using different loading conditions. The analytical solution provided upper and lower bounds for the center-point deflections of the panels, values potentially useful for hat-stiffened composite panels. The detailed FEA results accurately revealed the design sensitivities of relevant geometric parameters of hat-stiffened composite panels. The findings constitute a first step towards a structural and scripted FEA framework to speed the development and qualification of composite aircraft structures. The framework has the potential to reduce design cost, increase the possibility of content reuse, and improve time-to-market.